2020
DOI: 10.1126/sciadv.aaz0260
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide disrupts bacterial cytokinesis by poisoning purine metabolism

Abstract: Cytostasis is the most salient manifestation of the potent antimicrobial activity of nitric oxide (NO), yet the mechanism by which NO disrupts bacterial cell division is unknown. Here, we show that in respiring Escherichia coli, Salmonella, and Bacillus subtilis, NO arrests the first step in division, namely, the GTP-dependent assembly of the bacterial tubulin homolog FtsZ into a cytokinetic ring. FtsZ assembly fails in respiring cells because NO inactivates inosine 5′-monophosphate dehydrogenase in de novo pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 63 publications
8
14
0
Order By: Relevance
“…These results provide additional insight into the mechanism of NO-mediated stress, and suggest the response to NO is sufficient to arrest cell division, but not promote a stationary phase transition. This is consistent with published results showing NO disrupts cell division by arresting assembly of the FtsZ cytokinetic ring [46,47].…”
Section: Dsred 42 Signal Accumulation Correlates With Hmp Expression During Exposure To Acidified Nitritesupporting
confidence: 93%
“…These results provide additional insight into the mechanism of NO-mediated stress, and suggest the response to NO is sufficient to arrest cell division, but not promote a stationary phase transition. This is consistent with published results showing NO disrupts cell division by arresting assembly of the FtsZ cytokinetic ring [46,47].…”
Section: Dsred 42 Signal Accumulation Correlates With Hmp Expression During Exposure To Acidified Nitritesupporting
confidence: 93%
“…Our in vitro results were consistent with this, where exposure to NO was sufficient for TIMER42 signal accumulation. Our results are also consistent with a recently published study which showed that NO causes a collapse of proton motive force (PMF) and collapse of the divisome complex, thus resulting in cell division arrest (39). However, within host tissues, slow-growing bacterial cells with TIMER42 signal accumulation were largely Hmp -, and instead expressed the stationary phase marker, Dps.…”
Section: Discussionsupporting
confidence: 92%
“…These results provide additional insight into the mechanism of NO-mediated stress, and suggest the response to NO is sufficient to arrest cell division, but not promote a stationary phase transition. This is consistent with published results showing NO disrupts cell division by arresting assembly of the FtsZ cytokinetic ring (38,39).…”
Section: No Stress Is Sufficient To Promote Timer42 Signal Accumulationsupporting
confidence: 93%
See 1 more Smart Citation
“…6D). Similar to the uncoupler CCCP, NO also depolarizes the cytoplasmic membrane to arrest respiration and growth [48, 49]. Consistent with this, and as seen with CCCP, pretreatment with DETA-NO also increased basal OCR of wt Mtb and Mtb Δ sufR (Fig.…”
Section: Resultssupporting
confidence: 65%